(untitled) (Clinics, 2023)
Objectives: Isoflurane (ISO) is widely used in the clinic and research. The authors aimed to explore whether Neobaicalein (Neob) could protect neonatal mice from ISO-induced cognitive damage. Method: The open field test, Morris water maze test, and tail suspension test was performed to assess the cognitive function in mice. Enzyme-linked immunosorbent assay was used to evaluate inflammatory-related protein concentrations. Immunohistochemistry was used to assess Ionized calcium-Binding Adapter molecule-1 (IBA-1) expression. Hippocampal neuron viability was detected using the Cell Counting Kit-8 assay. Double immunofluorescence staining was employed to confirm the interaction between proteins. Western blotting was used to assess protein expression levels. Results: Neob notably improved cognitive function and exhibited anti-inflammatory effects; moreover, under iso-treatment, it exhibited neuroprotective effects. Furthermore, Neob suppressed interleukin-1β, tumor necrosis factor-α, and interleukin-6 levels and upregulated interleukin-10 levels in ISO-treated mice. Neob significantly mitigated iso-induced increases in IBA-1–positive cell numbers of the hippocampus in neonatal mice. Furthermore, it inhibited ISO-induced neuronal apoptosis. Mechanistically, Neob was observed to upregulate cAMP Response Element Binding protein (CREB1) phosphorylation and protected hippocampal neurons from ISO-mediated apoptosis. Moreover, it rescued ISO-induced abnormalities of synaptic protein. Conclusions: Neob prevented ISO anesthesia-induced cognitive impairment by suppressing apoptosis and inflammation through upregulating CREB1.